The temporal window of individuation limits visual capacity - Wutz, Andreas; Melcher, David (Frontiers in Psychology, 2014)
One of the main tasks of vision is to individuate and recognize specific objects. Unlike the detection of basic features, object individuation is strictly limited in capacity. Previous studies of capacity, in terms of subitizing ranges or visual working memory, have emphasized spatial limits in the number of objects that can be apprehended simultaneously. Here, we present psychophysical and electrophysiological evidence that capacity limits depend instead on time. Contrary to what is commonly assumed, subitizing, the reading-out a small set of individual objects, is not an instantaneous process. Instead, individuation capacity increases in steps within the lifetime of visual persistence of the stimulus, suggesting that visual capacity limitations arise as a result of the narrow window of feedforward processing. We characterize this temporal window as coordinating individuation and integration of sensory information over a brief interval of around 100 ms. Neural signatures of integration windows are revealed in reset alpha oscillations shortly after stimulus onset within generators in parietal areas. Our findings suggest that short-lived alpha phase synchronization (≈ one cycle) is key for individuation and integration of visual transients on rapid time scales (< 100 ms). Within this time frame intermediate-level vision provides an equilibrium between the competing needs to individuate invariant objects, integrate information about those objects over time, and remain sensitive to dynamic changes in sensory input. We discuss theoretical and practical implications of temporal windows in visual processing, how they create a fundamental capacity limit, and their role in constraining the real-time dynamics of visual processing.